Liquid chromatography and tandem mass spectrometric method for the quantification of Tepotinib in plasma samples - Arjun Siliveri, Kavitha Pingili (Journal of Applied Pharmaceutical Science, 2025)
A precise and accurate liquid chromatographic tandem mass spectrometric technique was developed to measure the levels of Tepotinib in plasma. Axitinib and Tepotinib were separated from the plasma sample solution using a protein precipitation method. A chromatographic isolation was carried out using a ZorbaxC18 stationary phase (2.1 × 100 mm, 3 μm) and mobile phase proportion of 0.1 % HCOOH and acetonitrile (15:85). The analytes were quantified using positive ionization methodology with electrospray ionization. Mass transitions for Tepotinib were m/z 493.23 → 296.17 and for Axitinib (IS) they were m/z 387.12 → 220.08. No interference from any components of blank plasma or additional substances was identified. Correlation between Tepotinib concentrations and the respective area of the peaks ratio to Axitinib showed a linear pattern across a range of 1.5–1200 ng/mL. The precision of Tepotinib was excellent, with an intra-day precision of ≤4.92% (n = 10) and an inter-day precision of ≤04.76% (n = 20, over three days). The measured average extraction recoveries of Tepotinib were 98.32%. Tepotinib underwent various stability tests at low and high-quality control levels. The results showed that Tepotinib remained stable and was within 95.41%–102.43%. The developed technique can be valuable for regular quantification of Tepotinib plasma samples in clinical organizations, various industries, and forensic laboratories.
Keywords: Tepotinib, lung cancer, plasma, LC-MS/MS, validation